Perancangan Sistem Informasi Transaksi Pembelian Dan Penjualan Beserta Persediaan Stok Produk Pada CV. Sumber Rezeki Jambi - Stefani, Dina Maria; Jusia, Pareza Alam; Mery (Jurnal Manajemen Teknologi Dan Sistem Informasi (JMS), 2024)
CV. Sumber Rezeki Jambi is one of the shop that are located in Jambi city management the purchasing and selling still use book so problems occur namely that is the slow process for finding data because have to open one by one note has been saved, sometimes the wrong recording the names of goods , goods price and the reckoning total sales, the difference between stock intermediate product products chronicled in the physical in a warehouse, and process of report that takes time and sometimes implementation has been delayed. For that reason, this study aims to give solution to problems that occur by offering information system of purchasing and selling use PHP programming language and MySQL DBMS. To the development of the system with a waterfall and adopting a unified system model language using use case diagrams, activity diagram, class diagrams and flowchart. The new system produces an output that data showing customers, the suppliers, the goods, purchasing and the selling data in structured and display reports needed to facilitate CV. Sumber Rezeki Jambi in obtaining information quickly and correctly.